Hubungan Pengetahuan Terhadap Sikap Remaja Putri Dalam Penanganan Dismenore Di Sma Assanadiyah Palembang Tahun 2016: Relationship between Knowledge and Attitudes of Young Women in Handling Dysmenorrhea in Palembang Senior High School in 2016 - Ratna Dewi (Institute Of Computer Science (IOCS), 2019)
The incidence of dysmenorrhea in Indonesia is 64.25%, consisting of 54.89% of primary dysmenorrhea and 9.36% of secondary dysmenorrhea. Dysmenorrhea is pain during menstruation that feels lower abdomen and appears before, during and after menstruation. Dysmenorrhea can have a negative impact on daily activities that often occur in adolescents who experience anxiety, tension and anxiety. The purpose of the study was to determine the relationship between Knowledge of the attitudes of young women in the treatment of dysmenorrhea in Palembang's Assanadiyah High School in 2016. The study design used analytical surveys with Cross Sectional research designs. Univariate and bivariate analysis by using Chi-Square statistical tests with a computerized system with the help of the SPSS program. The study population was all young women who experienced dysmenorrhea at Palembang Assanadiyah High School, March 11-14 2016. The sample of the study was total sampling technique, totaling 16 respondents. The results of bivariate analysis with chi-square statistical test showed p_value 1,000> ? 0,05, so there was no significant (significant) relationship of knowledge about the attitudes of young women in handling dysmenorrhea in Palembang Assanadiyah High School in 2016. The school was expected to provide reproductive health education about menstruation and dysmenorrhea so that the knowledge of young women about the treatment of dysmenorrhea is getting better.